2016
DOI: 10.1002/ep.12464
|View full text |Cite
|
Sign up to set email alerts
|

Biodesulfurization from the high sulfur coal with a newly isolated native bacterium, Aspergillus sp. DP06

Abstract: In this paper, we made attempt to desulfurize the coal collected from Yihai coalfield of Qinghai province in China contains high total sulfur content (4.97% by mass) and high organic sulfur content (3.37% by mass). The high sulfur coal sample was subjected to desulfurization by using a new bacterium isolated from the native coal mine site. The molecular identification of the 18S rRNA gene showed that the native bacterium was Aspergillus sp., denoted as DP06, and it is reported first time for the capability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…From Figure 5B, the total desulfurization rate of 38.78% was obtained after 15 days of leaching experiment, removal of organic sulfur of 81.45%, and removal of inorganic sulfur of 10.38%. The desulfurization rate of organic sulfur was better than most of the reported results, [27][28][29] which indicated that the strain SX-12 has a good ability of organic sulfur removal. However, the desulfurization rate is lower than the shake flask test result, which may be a more complete contact area between bacteria and coal in the shaking test.…”
Section: "Two-step" Leaching Biodesulfurization Testmentioning
confidence: 55%
See 1 more Smart Citation
“…From Figure 5B, the total desulfurization rate of 38.78% was obtained after 15 days of leaching experiment, removal of organic sulfur of 81.45%, and removal of inorganic sulfur of 10.38%. The desulfurization rate of organic sulfur was better than most of the reported results, [27][28][29] which indicated that the strain SX-12 has a good ability of organic sulfur removal. However, the desulfurization rate is lower than the shake flask test result, which may be a more complete contact area between bacteria and coal in the shaking test.…”
Section: "Two-step" Leaching Biodesulfurization Testmentioning
confidence: 55%
“…In recent years, 93% of electric power is produced from coal in South Africa, 79% in China, 78% in Australia, 68% in India, and 39% in America . However, a large amount of SO 2 and other sulfur‐containing gases was released into the atmosphere in the process of high‐sulfur coal combustion, resulting in environmental problems such as acid rain and haze With the depletion of high‐quality coal resources, the proportion of high‐sulfur coal consumption is increasing. Therefore, developing an effective mechanism that is capable of reducing the sulfur content of high‐sulfur coal becomes a hotspot in energy and environmental fields .…”
Section: Introductionmentioning
confidence: 99%
“…They used K-edge X-ray absorption near-edge structures to analyze the changes in the form of sulfur before and after desulfurization and found that the pyritic sulfur content of the coal decreased from 53.6% to 39.2%. Liu et al (2017) observed desulfurization of Yihai coalfield contains 4.97% total sulfur content. After desulfurization process with a newly isolated native bacterium Aspergillus sp.…”
Section: Introductionmentioning
confidence: 94%
“…Using a newly isolated heterotrophic bacterial strain Fusarium oxysporum FE, Etemadzadeh et al 4 removed 34.21% of sulfur from high‐sulfur coal collected from the Zobahan Factory in Isfahan. Also, Liu et al 12 investigated the bioleaching of Yihai coals and obtained a maximum total sulfur removal of 47% by using a fungal strain, Aspergillus sp. DP06.…”
Section: Introductionmentioning
confidence: 99%